Occupational exposure to noise and whole-body vibration in farmers of the Northern Area of Cartago, Costa Rica - Araya-Solano, Tannia (2020)
The use of tractor in the agricultural sector is very common, the physical agents associated with it use are noise and vibrations of the whole body; the objective of this project was to determine occupational exposure to these agents during the use of the tractor in 13 small companies of the northern zone of Cartago, Costa Rica. The exposure were measurement with the ISO 2631-1: 2001 and noise dosimeter. As a result, it was obtained that daily vibration exposure levels are above the action level in 53,8% of cases, and the noise level is between 54,8dB(A) a 75,4 dB(A), below occupational level exposure. The risks factors identified were related to the model and devices used in the equipment, postures and body mass index. The main conclusion is that the exposure to whole body vibration may cause health problems in the term, the model and devices used in the equipment are a risk factor of the exposure.